Dynamical modeling and simulation of pv-solar pannels - Junior, Antonio C. P. Brasil (Revista Brasileira de Energia Solar, 2017)
This paper explores a dynamical model of the thermal and electrical behavior of solar photovoltaic module. A detailed heat transfer model is implemented, coupled to an electrical model that takes into account all effects of cell temperature dependence in the variables of a single diode equivalent circuit. Radiation and convection heat transfer are considered, as well as the effect of thermal inertia. Simulations for the unsteady power output are obtained for typical variations of irradiation (ramps and valleys) and other real climatic inputs. A comparison between the dynamical and steady state models is discussed and the main differences for the temperature and power levels have shown the framework of applicability of the proposed model.